Assessing Life Balance During the Early Phase of COVID-19 Physical Isolation in Iranian Society - Sepideh Nazi; Somayeh Kavousipor; saeedeh Pourahmad; Farzaneh Yazdani; Mehdi Rezaee; Sahar Ghanbari (Shiraz University of Medical Sciences, 2024)
Background: This study explored the concept of 'life balance' during physical isolation due to COVID-19 in Iran in 2020. Methods: In a cross-sectional design, 403 participants completed the internet-based "Life Balance Inventory (LBI)", which includes five subscales: health, relationship, identity, challenging/interesting activity, and daily activities. The data were analyzed using SPSS 21, and a significant level of less than 0.05 was considered. Descriptive statistics, t-tests, and one-way ANOVA were utilized in the analysis. Results: The total mean score of LBI was 1.51+_0.38(unbalanced). The scores were distributed among the participants as follows: 52.6%  of participants scored between 0.6 and 1.5 (very unbalanced);  37.7% of participants scored between 1 and 1.5 (unbalanced); 8% of participants scored between 2 and 2.5 (moderately balanced); and finally, 1.7% of participants scored between 2.5 and 3 ( very balanced). Significant relationships were found between LBI and gender (P=0.001), chronic comorbidity (P-value =0.029), and Job (P-value=0.044). The health subscale showed no statistical difference according to the demographic factors. Males demonstrated more life balance in their daily activities, including driving and social transportation (p=0/001). Married participants and those older than 40 exhibited more balance in the relationship subscale (p-value=0/001). Teachers and faculty members showed more balance in identity (p=0.014) and relationship (p=0.001). Higher-income participants revealed more life balance in the challenge/interesting subscale (p=0.033). Conclusion: The results suggested that participants experienced an unbalanced lifestyle during the early phase of COVID-19 isolation.